Analysis of hybrid solar biomass power plant for generation of electric power. (2022) - Kaur, Harpreet; Gupta, Surbhi; Dhingra, Arvind
Abstract: The need of world electricity production is growing at an increasing rate and because of its limited supply, it cannot completely be met by ordinary energy framework. The use of hybrid systems by renewable electricity sources for energy generation has also created considerations in general. There is no one source of renewables ready to continuously load electricity, and hybrid systems are thus a key solution. Renewable energy is produced by inexhaustible reserves, usually refilled on a human scale, such as sun, wind, hydro, mainstay, biomass, etc. In four core areas, renewable energy often provides energy: electricity, air and water heating/cooling, transport, and rural (stand-alone and network) energy services. In comparison with other sources, renewable power sources have reserves in large geographical regions amassed in a small number of countries. Rapid organization of renewable energy sources and energy conservation brings enormous energy stability, ecological change relief and financial benefits. Hybrid systems (PV-Biomass) are used in different regions to provide electricity to overcome discontinuity and transition in solar and wind power. This paper discusses the techno-economic feasibility analysis of solar biomass system in the Ludhiana district of Punjab.